Solusi Persamaan keseimbangan Massa Reaktor Menggunakan Metode Pemisahan Variabel - Arif, Mohammad Syaiful; Jamhuri, Mohammad (CAUCHY, 2015)
Mass balance of reactor equation express the change of mass concentration of substances in and out of the closed system. This equation has inhomogeneous boundary conditions, that is the conditions at the time of its entry to the reactor and the conditions under which the substance out of the reactor. In this study, the mass concentration of substances produced after the reaction in the reactor is zero. In the inhomogeneous boundary conditions, using the method of separation of variables, there are obstacles to complete the equation. So we need to first transformation. Transformation is done with the aim to change the conditions which originally inhomogeneous boundary into a homogeneous boundary condition, so the method of separation of variables can be used to solve partial differential equations that have a homogeneous boundary conditions. The results obtained by the analysis, the faster a substance that spreads to the reactor, the less amount of mass concentration of substances that undergo a change; the greater the mass coefficient of substances that react in the reactor, the more the number of mass concentration of substances that are subject to change